Cytokine-induced reprogramming of human macrophages toward Alzheimer’s disease-relevant molecular and cellular phenotypes in vitro - Anna Podleśny-Drabiniok; Carmen Romero-Molina; Tulsi Patel; Wen Yi See; Yiyuan Liu; Edoardo Marcora; Alison M. Goate (Cell Reports, 2025)
Summary: Myeloid cells, including brain-resident microglia and peripheral macrophages, play key roles in neurodegenerative diseases such as Alzheimer’s disease (AD). Studying their disease-associated states is limited by the lack of robust in vitro models. Here, we test whether a cytokine mix (interleukin [IL]-4, CSF1, IL-34, and transforming growth factor-β) reprograms human THP-1 macrophages toward AD-relevant phenotypes. This treatment induces significant transcriptomic changes, driving THP-1 macrophages toward a transcriptional state reminiscent of disease-associated microglia and lipid-associated macrophages (LAM), collectively referred to as DLAM. Transcriptome profiling reveals gene expression changes related to oxidative phosphorylation, lysosome function, and lipid metabolism. Single-cell RNA sequencing shows an increased proportion of DLAM clusters in cytokine mix-treated THP-1 macrophages. Functional assays demonstrate alterations in cell motility, phagocytosis, lysosomal activity, and metabolic profiles. These findings provide insights into cytokine-mediated reprogramming of macrophages toward disease-relevant states, highlighting their role in neurodegenerative diseases and potential for therapeutic development.